0148 Assessment of Sleep Depth and Propensity during Sleep Restriction using the Odds-Ratio-Product. (27th April 2018) - Schweitzer, P K; Griffin, K S; Younes, M; Walsh, J K
Abstract: Introduction: The Odds-Ratio Product (ORP) is a continuous measure of the relative power in four EEG frequency bands. ORP ranges from 0 (deep sleep) to 2.5 (full wakefulness). A prior study of patients with sleep disorders revealed excellent correlation between ORP during any sleep epoch and probability of arousal occurring in the next 30 seconds (r 2 =0.98), suggesting it may serve as a measure of sleep depth and propensity. To further test this hypothesis, we determined the response of ORP produced by sleep restriction (SR), using a previously-published data set in which delta/theta power was reported to show no change during the first two SR nights and a marginal increase during the subsequent two SR nights. Methods: Twenty-one healthy subjects (12 f; age 32.0 ± 9.9y) underwent two 8-9h PSGs (baseline) followed by four consecutive nights of SR (5 h/night, starting 1:00 AM). ORP was measured at 3-second intervals and averaged over individual sleep stages, total sleep time (TST), and total recording time (TRT). ORP values from the SR nights were compared to the corresponding values in the first 5 hours of baseline night 2. Results: Relative to baseline, ORP decreased significantly during wake epochs in each of the four SR nights (-4.1 ± 3.0%, -5.1 ± 5.8%, -4.5 ± 6.4%, and -9.8 ± 7.8% of baseline, respectively; P<0.01 for all nights). As predicted, there were no significant ORP changes in any sleep stage on SR night 1. ORP decreased significantly in all sleep stages during each of the subsequent three SR nights. Magnitude of change from baseline in ORP (ΔORP) varied considerably among subjects; decreases of 0%-50% for ORP in TRT and 0%-28% for ORP in TST. In two subjects ORP increased consistently during SR. ΔORP was consistent within each subject across the last three SR nights (r>0.78 for all comparisons). Conclusion: ORP behaves as expected during sleep restriction. Additionally, ORP appears more sensitive than delta/theta power in detecting change in sleep pressure. Moreover, wake ORP is sensitive to sleep pressure. There are considerable, but consistent, differences in ORP response among individuals. Support (If Any):